2023
DOI: 10.1108/jic-05-2023-0112
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of employer brand attributes on financial performance: an intellectual capital perspective

Vladimir Dženopoljac,
Jasmina Ognjanović,
Aleksandra Dženopoljac
et al.

Abstract: PurposeThe employer brand is a crucial intangible asset for companies as it enhances the employer–employee relationship, leading to improved employee performance and overall company outcomes. This paper aims to investigate the contribution of the employer brand to the financial results of companies in southern Europe.Design/methodology/approachThe sample consists of 266 companies operating in southern European countries during the year 2020. Secondary data on employer brand attributes, assessed from the perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
(211 reference statements)
0
1
0
Order By: Relevance
“…A study by Yousaf and Dey (2022) revealed that ROA is the best proxy to measure firm performance after analyzing 297 Czech firms' data from three sectors. However, ROA and ROE are the most common proxies used in the previous literature (Dženopoljac et al, 2023;Habib and Dalwai, 2023;Kayakus et al, 2023;Nawaz and Ohlrogge, 2022;Olohunlana et al, 2022;Kayani et al, 2020;Ahmed and Bhuyan, 2020;Samo and Murad, 2019). Therefore, both ROA and ROE are employed as proxies to measure firm performance in the present research.…”
Section: Firm Performancementioning
confidence: 99%
“…A study by Yousaf and Dey (2022) revealed that ROA is the best proxy to measure firm performance after analyzing 297 Czech firms' data from three sectors. However, ROA and ROE are the most common proxies used in the previous literature (Dženopoljac et al, 2023;Habib and Dalwai, 2023;Kayakus et al, 2023;Nawaz and Ohlrogge, 2022;Olohunlana et al, 2022;Kayani et al, 2020;Ahmed and Bhuyan, 2020;Samo and Murad, 2019). Therefore, both ROA and ROE are employed as proxies to measure firm performance in the present research.…”
Section: Firm Performancementioning
confidence: 99%
“…Moreover, firms need to invest in human capital to increase their value (Backhaus & Tikoo, 2004). Given this fact and the need to be an attractive employer (Immerschitt & Stumpf, 2014), employer branding has gained importance in recent years (Backhaus & Tikoo, 2004;Berthon et al, 2015;Dženopoljac et al, 2023).…”
Section: Introductionmentioning
confidence: 99%